Implementation of targeted screening for lung cancer in a high-risk population within routine NHS practice using low-dose computed tomography. Issue 4 (3rd March 2020) - Grover, Helen; Ross, Thomas; Fuller, Elizabeth
Abstract : We report a primary care-based lung cancer targeted screening programme using low-dose CT (LDCT) in South Tyneside and Sunderland. Ever smokers with ≥10 pack-years aged 55–74 years were identified at annual COPD review. 925 individuals attended for LDCT. 2% (n=19/925) had lung cancer diagnosed. 66.7% (n=14/21) had early stage disease and 78.9% (n=15/19) were offered treatment with curative intent. 79.3% of individuals attending for LDCT were ranked in the lowest deprivation quintiles. This approach has been successfully established in routine NHS practice; it is effective with improvements in stage of disease and engages individuals in deprived areas.